Au revoir gophère: Creative innovation in golf course architecture, retrospective judgments of quality, and magazine golf course rankings - Daniel A. Ackerberg; Douglas J. Hodgson (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2022)
In the various fields of creative, cultural, and artistic production, there exists a competitive struggle amongst creators of innovative works or ideas to persuade agents in the field to accept and value the new work. This is a significant challenge since cultural innovators do not produce in response to existing demand, but must create new demand for what they are supplying (Bourdieu (1996)). A common polemical tactic is to demarcate the new style from existing predominant ones by appealing to and extolling the virtues of a still earlierstyle that is maintained to have classic historical status, and thus lacking the corruption or excess of the prevailing style. The proposed innovation is purported, by the creators themselves or the critics who champion them, to renew the classic principles of the historic style, and in their polemic the new breed of creators attempt to persuade the field to revaluate the historic style, and thus by affinity the new style, to the detriment of the prevailing style, which must be devalued. Current evaluative judgements of the relative merits of past and existing styles are thus revised, in favour of the former. This evolution in retrospective judgement of styles can in principle be measured. In the field of golf course architecture, the stylistic revolution unleashed in the early 1990's was accompanied by the new architects and their critics extolling the pre-war "Golden Age" of architecture to the detriment of what they called the "Dark Ages" of post-war architecture. We measure the effect of this polemic on the field's overall judgment through an empirical analysis of 30 years of widely read and discussed biannual rankings of the 100 Greatest Courses in the United States as assembled and published by the major magazines Golf Digest and Golf Magazine, and find significant evidence that the rankings evolved during this period in favour of pre-war courses as opposed to post-war courses built before 1990.
Keywords: Z11; Z20; 330; economics of golf; economics of the arts; endogenous preferences; Bourdieusian distinction